State-Of-Art Review of Shrinkage Effect on Cracking and Deformations of Concrete Bridge Elements - Viktor Gribniak; Gintaris Kaklauskas; Darius Bacinskas (The Baltic Journal of Road and Bridge Engineering, 2007)
Present state-of-art review deals with concrete shrinkage influence on cracking resistance and deformations of structural elements of concrete bridges. It has been shown that shrinkage deformations are one of major causes of defects in bridge structures in over the world. Various factors that influence the behaviour of the shrunk members have been discussed. The paper illustrates behaviour of a restrained member due to shrinkage and accompanying creep. For increasing crack resistance of concrete bridge structures the research recommends using lower cement contents and shrinkage reducing admixtures. Other measures are performing mixtures with slightly higher water/cement ratios, reducing the amount of reinforcing steel in the bridge elements and eliminating structural restraints.